Doxorubicin hydrochloride‐loaded electrospun poly(l‐lactide‐co‐ε‐caprolactone)/gelatin core–shell nanofibers for controlled drug release. Issue 12 (22nd July 2021) - Wang, Lei; Huang, Yifan; Xin, Binjie; Li, Tingxiao
Abstract: Electrospun core–shell nanofibers have aroused attention in drug delivery systems and tissue engineering because of the latent structures which can encapsulate various drugs and obtain tailored release profiles. Here, poly(l ‐lactide‐ co ‐ε‐caprolactone) (PLCL) with gelatin (GE) blends were employed to electrospin the shell of core–shell nanofibers which could act as a protection layer for the controlled released behavior of the model drug doxorubicin hydrochloride (DOX). Core–shell nanofiber membranes with different drug loaded amounts were fabricated and the corresponding drug release behaviors were researched. The surface morphology of the obtained nanofibers was assessed by SEM and the structure of the core–shell nanofibers were observed by inverted fluorescence microscopy and TEM. The hydrophilicity was evaluated by water contact angle testing and the results indicated that the obtained fibers all possess good hydrophilicity. The mechanical properties of the fiber membranes were evaluated by tensile testing. Exploring the composition of the fiber membranes by Fourier transform infrared spectroscopy proved that DOX existed in the drug‐loaded fiber membranes. In vitro release was evaluated by UV–visible spectroscopy and the accumulative release curves of DOX showed that increasing drug rates would lead to increasing cumulative release amounts but decreasing cumulative drug release rates. The results indicated that drugs encapsulated in PLCL/GE core–shell nanofiber material would be efficient and a potential material for drug delivery systems. © 2021 Society of Chemical Industry Abstract : The hydrophilicity of the nanofibers was improved; the model drug doxorubicin hydrochloride (DOX) was successfully encapsulated into the core layer of poly(l ‐lactide‐ co ‐ε‐caprolactone)/gelatin (PLCL/GE) nanofibers and continuous release behaviors were obtained.